Detection of Homologous Blood Transfusion in Sport Doping by Flow Cytofluorimetry: State of the Art and New Approaches to Reduce the Risk of False-Negative Results - Francesco Donati; Xavier de la Torre; Sarajane Pagliarosi; Daniela Pirri; Giuliana Prevete; Francesco Botrè; Francesco Botrè (Frontiers Media S.A., 2022)
This article presents the results of a study aimed to give new suggestions and strategies for improving the implementation of the flow cytofluorimetry-based method for the detection of homologous blood transfusions in doping control. The method is based on the recognition of the phenotypic mismatch between minority blood group antigens possessed by the donor and the recipient. Two strategies have been followed to reduce the risk of false-negative results: (i) the monitoring of a broader range of erythrocytes surface antigens; and (ii) the application of different surface erythrocyte staining protocols, tailored on the different antigens and the type of antigenic mismatch that had to be detected (whether it is the donor or the recipient who expresses or not the antigen to be detected). Special attention has also been focused on the time factor, to avoid prolonged sample storage, since hemolysis may have a significant impact on the reliability and quality of the results. Our experimental evidence suggests that the risk of false-negative results can be minimized by (i) the expansion of the antigen panel, with the inclusion of four additional targets; (ii) a more accurate selection of the gating area of the red blood cells; (iii) the choice of a better fluorochrome (alexa fluor 488) to be conjugated to the secondary antibody; and (iv) the implementation of different staining protocols depending on the nature of the double population to be detected (donor expressing vs. recipient non-expressing and vice versa). The combination of the above approaches allowed a significant reduction of false-negative results, assessed on samples simulating a homologous blood transfusion between two compatible subjects.